The Effect of Knowledge Sharing and Interpersonal Trust on Innovation: An Empirical Study in Indonesia Higher Education - Johan, Muhammad (IJOSMAS, 2021)
This study investigates the effect of interpersonal trust among private university lecturers in Tangerang (i.e., trust in co-workers and leaders) on innovative behavior and examines the mediating effect of knowledge sharing on these relationship. A total of 74 lecturers from a private university in Tangerang participated in this research. The results revealed that trust in co-workers and trust in leaders had a positive effect on knowledge-sharing activities. Although the effect of trust in co-workers on innovative behavior is not significant, trust in leader has a significant effect on innovative behavior. The effect of lecturer knowledge sharing on innovative behavior was also found to be significant. In addition, the results showed that knowledge sharing had a full mediating effect on the relationship between trust in co-workers and innovative behavior and a partial mediating effect on the relationship between trust in leader and innovative behavior.